ANALISIS PERBANDINGAN KINERJA REKSADANA SAHAM SYARIAH DAN REKSADANA SAHAM KONVENSIONAL - Gafar, Muammar Saidul; jasman, jasman (Sekolah Tinggi Ekonomi Dan Bisnis Islam Darussalam, 2020)
The purpose of this research is to determine the comparative analysis between the performance of sharia equity mutual funds and conventional equity mutual funds in Indonesia Stock Exchange. Sampling methods that the authors do by using purposive sampling are listed in the Indonesia Stock Exchange during the period from 2011 to 2015. Retrieved 23 samples consisted of mutual fund shares 6 sharia equity mutual funds and 17 conventional equity mutual funds. Data analysis techniques using normality test to determine the level of distribution of data was donwloaded, and then data was analyzed with independent sample t test. Based on analysis of data, I do that there are two different methods of calculation the performance with the Sharpe method and Jensen Alpha method and a method of no differ the performance of sharia equity mutual funds and conventional equity mutual funds at the Treynor method. Based on the test results Independent sample t test of Sharpe methods significant value of the comparative performance of Islamic equity mutual fund and conventional equity mutual fund is 0,014, meaning that there is a significant difference performance of sharia equity mutual fund and conventional equity mutual funds. The test results of independent samples t test method Treynor significant value of mutual fund performance comparison of Islamic and conventional equity mutual fund is 0.386, the meaning that there is no significant difference in the performance of sharia equity mutual funds and conventional equity mutual funds. And Jensen Alpha method calculation results using independent test sample t test, significant value is 0.023, the meaning that there is a significant difference between the performance of sharia equity mutual funds and conventional equity mutual fund.